A retrospective study of tunnelled haemodialysis central line-associated bloodstream infections. (3rd April 2019) - Krishnan, Anoushka; Irani, Khushnam; Swaminathan, Ramyasuda; Boan, Peter
Abstract : Infection is a serious complication of tunnelled haemodialysis catheters. We aimed to describe the epidemiology of tunnelled haemodialysis central line-associated bloodstream infections (CLABSI) in an Australian centre. We performed a retrospective audit of tunnelled haemodialysis CLABSI from June 2010 to June 2014. From 674 catheter insertions, 70 CLABSI occurred in 55 patients at a rate of 0.95 infections per 1000 catheter days. Aboriginal and Torres Strait Islanders (ATSI) compared to non-ATSI had a higher rate of CLABSI (1.70 vs 0.58 CLABSI per 1000 catheter days, p  < 0.001). Staphylococcus aureus ( n  = 22, 31.4%), coagulase negative Staphylococci ( n  = 14, 17.5%), and Gram negative bacilli ( n  = 28, 35.0%) were the predominant causative organisms. Two patients who died both had Staphylococcus aureus infection. In conclusion, our infection rate and microbiology are similar to prior reports. Morbidity and mortality are associated with Staphylococcus aureus as the causative organism.